2005
DOI: 10.1021/ja050602o
|View full text |Cite
|
Sign up to set email alerts
|

Supercapacitive Admittance Tomoscopy

Abstract: Abstract:A sensor for measuring adsorption on a substrate has been designed including a contactless detection scheme, called supercapacitive admittance tomoscopy (SCAT). The sensor comprises a thin dielectric layer with two parallel band electrodes on the one side and a chemically modified surface on the other onto which the adsorption of molecules occurs. Upon application of a high frequency ac voltage between the two electrodes, a capacitive coupling is established across the dielectric layer, and the admitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
4

Year Published

2005
2005
2014
2014

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 29 publications
(26 reference statements)
0
31
0
4
Order By: Relevance
“…However, in the previous study [10], the impedance between the microelectrodes and the microchannel through the bulk of the PET substrate was not considered since it has been reported that the resistance is large enough that it could be disregarded. Thus, impedance measurements performed here are undertaken on the device when it is empty or filled with a sodium chloride solution in order to reach a better understanding of the PET impedance contribution in the global response.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, in the previous study [10], the impedance between the microelectrodes and the microchannel through the bulk of the PET substrate was not considered since it has been reported that the resistance is large enough that it could be disregarded. Thus, impedance measurements performed here are undertaken on the device when it is empty or filled with a sodium chloride solution in order to reach a better understanding of the PET impedance contribution in the global response.…”
Section: Resultsmentioning
confidence: 99%
“…The microchip device used in this work was described elsewhere [10,13]. Some modifications have been made and will be outlined hereafter.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the same concept, non-contact impedance spectroscopy through polymer microchannel provides a thorough method for probing biomolecular interactions on insulated materials [10] with related applications in sensors [11,12], DNA-sensors [6,7], and enzyme biosensors [13]. With this non-conventional impedance spectroscopy, since the embedded microelectrodes are not in direct contact with the solution, the alternating potential difference imposed between the two microelectrodes is modulated in high frequency range.…”
Section: Introductionmentioning
confidence: 99%